Promoting online collaborative learning on moodle platform with the “quick chat” plugin - Dello Iacono, Umberto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In recent years, several Vygotskian computer-based learning activities (VCBLAs) were designed in the context of (mathematics) education and implemented on Moodle platform. However, Moodle does not allow users to visualize all chats on a single browser page, and they are forced to open multiple browser windows and switch among them very frequently. This paper describes the features of a plugin for Moodle, called “Quick Chat,” which allows to manage in a single browser window both the narrative flow of a VCBLA and all chats. Some results of an experimentation with PhD students, engaged in solving two mathematical tasks, are shown.